Development of the Bereavement and Interpersonal Domains codebook. Issue 4 (21st April 2022) - Ogle, Christin M.; Liu, Alexander G.; Fisher, Joscelyn E.; Ali, Bilal; Rasmussen, Andrew; Cozza, Stephen J.
Abstract: We describe the development of an empirically-derived codebook for qualitative data concerning the impact of grief on the interpersonal relationships of bereaved individuals. Relatives ( N  = 39) of deceased military service members participated in focus groups concerning how grief influenced their relationships across multiple interpersonal domains, including family, friends, community, and with the deceased. Focus group transcripts were coded using a stepwise process consistent with grounded theory to identify and categorize recurrent themes. The process yielded a comprehensive codebook containing 44 nodes with definitions and examples. The codebook provides researchers with an empirically-grounded analytic tool for future studies on bereavement.